A gender-transformative approach to improve outcomes and equity among persons with traumatic brain injury. Issue 5 (19th May 2019) - Mollayeva, Tatyana; Amodio, Vanessa; Mollayeva, Shirin; D'Souza, Andrea; Colquhoun, Heather; Quilico, Enrico; Haag, Halina (Lin); Colantonio, Angela
Abstract : Introduction: The initiation and translation of sex-sensitive and gender-sensitive research programmes into clinically useful considerations for patients with traumatic brain injury (TBI) have been difficult. Clinical frameworks are currently not specific according to sex and gender, despite evidence that these constructs influence the incidence, course and outcome of patients with TBI. The present protocol outlines a strategy for a research programme, supported by the Canadian Institutes of Health Research (CIHR) Institute of Gender and Health, which explores sex and gender topics in the context of TBI, with the goal of building an infrastructure to facilitate the implementation of sex/gender-sensitive research findings into clinical considerations. Methods and analysis: A comprehensive multistep research programme is proposed to support three research objectives: (1) documentation of important concepts and ideas for education on topics of sex and gender in the TBI context using a knowledge-user feedback framework, current scientific evidence and the research team's expertise; (2) development of educational materials for patients with TBI, significant others and clinicians providing care that account for sex/gender and (3) testing the application of these educational materials for feasibility and effectiveness. This programme supports the CIHR Institute's mission by facilitating partnership with knowledge users across clinical, research, academic and community sectors, through a range of platforms and activities. Ethics and dissemination: The Research Ethics Board of the University Health Network has approved the programme. It is anticipated that this work will add significant value to the advancement of the field of sex, gender and health by serving as a model to foster the integration of these constructs across the spectrum of disorders. This will transform clinical practices and ensure that generated knowledge is translated into improved training programmes, policies and health services that are responsive to the diverse needs of men and women with TBI. PROSPERO registration number: CRD42018098697